Uji Aktivitas Antikoagulan Ekstrak Daun Ciplukan (Physalis Angulata L) Secara Invitro: Anticoagulant Activity Test of Ciplukan Leaf Extract (Physalis Angulata L) Invitro - Uswatun Khasanah Duri Putri; Hajrah Hajrah; Adam M. Ramadhan (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Ciplukan leaf (Physalis angulata L) is empirically used as a hypercoagulation drug. The content of flavonoid secondary metabolites has potential as an anticoagulant. This study aims to determine the yield of ciplukan leaf extract and fraction, the content of secondary metabolites, and its activity as an anticoagulant. The method used in testing anticoagulant activity is Lee White and blood smear. Ciplukan leaves was extracted by maceration method using 70% ethanol solvent. The test samples for the extract and fraction of ciplukan leaves were made in 3 variations of concentration, that is 0.1%; 0.5%; and 1%. The results of ciplukan leaf extract, n hexane fraction, ethyl acetate and distilled water fraction were 14.284%; 12.9%; 10%; and 19.5%. The results of the phytochemical screening test of 70% ethanol extract contain secondary metabolites of flavonoids, alkaloids, tannins, phenols, saponins, steroids, triterpenoids. n?hexane fraction contains alkaloids, steroids and triterpenoids. The ethyl acetate fraction contains flavonoids, phenols and tannins. While the distilled water fraction contains flavonoids, phenols, tannins and saponins. Based on the test results of the Lee White method, extracts and fractions of ciplukan leaves have anticoagulant activity where blood clots do not occur after 2 hours of observation. In the blood smear method, the blood cells are round and not clustered. The best test sample concentration is at a concentration of 1%. The anticoagulant activity of the positive control was better than that of the ciplukan leaf extract and fraction.